INTEGRASI COMPUTATIONAL THINKING DALAM PEMBELAJARAN PROYEK TOPIK ENERGI ALTERNATIF KELAS III SEKOLAH DASAR - Dwi Sartina; Shinta Maylani; Kintan Limiansih (Program Studi PGSD Universitas Flores, 2023)
The implementation of Computational Thinking (CT) integration in project-based learning on alternative energy topics has been carried out. This study aims to find out and hone the level of understanding of students in solving problems in alternative energy material. This research is a type of descriptive qualitative research. Respondents for this study were 19 class III students of SD Negeri Plaosan 1. The data collection method used was field observation and documentation. The data analysis technique uses descriptive data reduction, data display, and conclusion delivery. The results of the study show that the implementation of CT in elementary school learning of alternative energy materials can reveal all of CT's foundations, namely decomposition, pattern recognition, algorithms, and abstraction. In addition, the teacher's ability to carry out CT-integrated learning on alternative energy material achieves a score of 92% or includes